23rd International Conference on Paste, Thickened and Filtered Tailings - PASTE 2020 2020
DOI: 10.36487/acg_repo/2052_25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Linear and Central Distribution System for Thickened Tailings Stacking

Abstract: One of the key parameters in successful implementation of thickened tailings schemes for tailings management is the achievable tailings beach slope. Study of geomorphology and hydrodynamics of tailings beaches has shown that the achievable beach slope is directly proportional to tailings solids concentration (i.e. rheology) and inversely proportional to discharge flowrate.Splitting the total tailings flowrate from the process plant, into multiple spigots prior to discharge to a Tailings Storage Facility (TSF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Each has pros and cons in terms of hydraulics, operational challenges, and effectiveness in flow splitting and minimising flow remerging on the beach to achieve a uniform deposition and required beach slope. Overall, it is concluded that in most cases, the CDS is a more effective, easier to operate and less costly design in comparison to the LDS (Pirouz et al 2020).…”
Section: Tailings Distribution Systemmentioning
confidence: 96%
“…Each has pros and cons in terms of hydraulics, operational challenges, and effectiveness in flow splitting and minimising flow remerging on the beach to achieve a uniform deposition and required beach slope. Overall, it is concluded that in most cases, the CDS is a more effective, easier to operate and less costly design in comparison to the LDS (Pirouz et al 2020).…”
Section: Tailings Distribution Systemmentioning
confidence: 96%
“…In addition, uniform distribution and discharge of tailings into the TSF is a key element in filling the storage space evenly and optimising the effective storage capacity of the TSF. However, there is a limitation on the number of flow splits that will be possible at a given site, depending on the geometry of the storage and the filling method, as separate flow streams will tend to merge on the beach if the discharge spigots are too close to each other or leave unfilled spaces if the spigots are too far apart (Pirouz et al 2020).…”
Section: Main Tailings Distribution Systemsmentioning
confidence: 99%